Masala chai, fast and slow [book with audioplayer] - LaRocca, Rajani (Findaway World, LLC, 2024)
When his grandfather, who makes masala chai each morning for the family, sprains his ankle, impatient Aarav decides to make the chai himself, but when his rushing causes him to miss some crucial steps, he must learn to slow down to get the recipe right.